2017
DOI: 10.1038/srep44814
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of efficiency droop and internal electric field for InGaN blue lighting-emitting diodes on silicon and sapphire substrates

Abstract: We investigated the efficiency droop and polarization-induced internal electric field of InGaN blue light-emitting diodes (LEDs) grown on silicon(111) and c-plane sapphire substrates. The efficiency droop of the LED sample grown on silicon substrates was considerably lower than that of the identically fabricated LED sample grown on sapphire substrates. Consequently, the LED on silicon showed higher efficiency at a sufficiently high injection current despite the lower peak efficiency caused by the poorer crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 39 publications
3
29
0
3
Order By: Relevance
“…Recently, one of the authors of this paper reported the experimental results of the comparison between the device characteristics of InGaN/GaN blue LEDs grown on silicon and sapphire substrates [12]. The efficiency droop of the LED sample on silicon substrates was found to be significantly lower than that of the identically grown LED on sapphire substrates.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, one of the authors of this paper reported the experimental results of the comparison between the device characteristics of InGaN/GaN blue LEDs grown on silicon and sapphire substrates [12]. The efficiency droop of the LED sample on silicon substrates was found to be significantly lower than that of the identically grown LED on sapphire substrates.…”
Section: Introductionmentioning
confidence: 95%
“…В настоящее время растет интерес к полуполярным светодиодным гетероструктурам -светодиодным структурам на основе соединений GaN/InGaN [1][2][3]. Однако мощные коммерческие светодиоды изготавливаются на основе нитрида галлия, выращенного в полярном направлении [4,5]. Если в барьерных слоях GaN электрические поля возникают только изза спонтанной поляризации [6], то на гетерограницах GaN/InGaN присутствуют также и пьезоэлектрические поля, обусловленные механическими напряжениями.…”
Section: Introductionunclassified
“…Ранее оценка пьезоэлектрических полей в множественных КЯ светодиодных образцов GaN/InGaN, выращенных на сапфировой подложке методом газофазной эпитаксии, проводилась методами фотолюминесцении и рентгеноструктурного анализа (XRD) [8], а также методами электропоглощения и фототока [9]. В работе [5] проведено сравнение напряженности пьезоэлектрических полей светодиодных гетероструктур на основе InGaN, выращенных на кремниевой и на сапфировой подложках методами фотолюминесцении, электролюминесцении и электроотражения (ЭО). Сле-дует отметить, что электрические поля, возникающие в активной области с множественными КЯ, могут быть неоднородны, например, вследствие различия механических напряжений на гетерограницах по мере роста [10].…”
Section: Introductionunclassified
“…Epitaxially grown planar In x Ga 1−x N /GaN layers have become an industry standard for solid state white light emitters such as LEDs. In conventional planar quantum well structures, achieving efficient full visible spectrum emission has been challenging due to issues such as efficiency droop at high injection currents [1], large internal polarization fields [2,3] and a rapidly decreasing emission efficiency as a function of increasing InN concentration, known as the green gap [4][5][6].…”
mentioning
confidence: 99%